Part Time Job and Students’ Academic Achievement: A Case of Kathmandu Valley - Khaniya, Abhishek (Nepalese Journal of Business, 2024)
This study examines the part time job and students’ academic achievement: A case of Kathmandu Valley. Academic achievement is the dependent variable. The selected independent variables are no. of working hours in a week, job type, work schedule flexibility, workload intensity and duration of employment. The primary source of data is used to assess the opinions of respondents regarding no. of working hours in a week, job type, work schedule flexibility, workload intensity and duration of employment. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of part time job and students’ academic achievement: A case of Kathmandu Valley. The study showed a negative impact of no. of working hours in a week on academic achievement. It indicates that higher the no. of working hours per week, lower would be the academic achievement. Similarly, the study showed a positive impact of job type on academic achievement. It indicates that if there is an alignment between a student’s job type and their field of study, their academic achievement would be higher. Likewise, the study also revealed a positive impact of work schedule flexibility on academic achievement. It indicates that flexible working schedule leads to increase the academic achievement. Further, the study observed a negative impact of workload intensity on academic achievement. It indicates that higher the work load intensity lower, would be the academic achievement. In addition, the study observed a positive impact of duration of employment on academic achievement. It indicates that students with stable and consistent employment over an extended period tend to have higher academic achievement.